2001
DOI: 10.1042/0264-6021:3580681
|View full text |Cite
|
Sign up to set email alerts
|

Parameters affecting in vitro oxidation/folding of maurotoxin, a four-disulphide-bridged scorpion toxin

Abstract: Maurotoxin (MTX) is a 34-mer scorpion toxin cross-linked by four disulphide bridges that acts on various K(+) channel subtypes. MTX adopts a disulphide bridge organization of the type C1-C5, C2-C6, C3-C4 and C7-C8, and folds according to the common alpha/beta scaffold reported for other known scorpion toxins. Here we have investigated the process and kinetics of the in vitro oxidation/folding of reduced synthetic L-MTX (L-sMTX, where L-MTX contains only L-amino acid residues). During the oxidation/folding of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…8D and Table 3). As the PPIase concentration in the ER was not known, enzyme:substrate ratios concurrent with previous studies were used (40,56). In the presence of 0.5 M Conus PPI B folding was accelerated ϳ6-fold with a half-time of 100 min (77-141 min) (Fig.…”
Section: Conotoxin Folding Studies-to Investigate the Role Of Conusmentioning
confidence: 82%
See 2 more Smart Citations
“…8D and Table 3). As the PPIase concentration in the ER was not known, enzyme:substrate ratios concurrent with previous studies were used (40,56). In the presence of 0.5 M Conus PPI B folding was accelerated ϳ6-fold with a half-time of 100 min (77-141 min) (Fig.…”
Section: Conotoxin Folding Studies-to Investigate the Role Of Conusmentioning
confidence: 82%
“…A number of proteins have been identified as in vivo (30,38) and in vitro (19,39) folding substrates for PPIases; however, little is known about their role in the folding of small cysteine-rich peptides. In the only study reported to date, the effects of the human cytosolic PPIase FKBP-12 on the oxidative folding of the scorpion toxin maurotoxin were evaluated (for sequence see Table 1) (40). The presence of PPIase accelerated the disappearance of intermediate folding species but does not change the overall folding kinetics of maurotoxin in vitro (40).…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, bovine PDI also facilitates folding of cyclotides. This is not unexpected, since bovine PDI has also been shown to facilitate folding of other nonbovine disulfide-rich peptides, including examples from cone snails and scorpions (39,40). The final yield of correctly folded cyclic peptide in the presence of OaPDI was about 4-fold greater than that of the linear peptide, although the folding rate was about 3-fold greater for linear kalata B1.…”
Section: Reducedmentioning
confidence: 99%
“…The complete chemical synthesis of a toxin with only D-amino acids has been seldom reported. In one pioneering work, Di Luccio et al (42) reported the chemical synthesis of D-maurotoxin, a four-disulfide-bridged toxin active on potassium channels. Interestingly, the kinetic features of the in vitro oxidation/ folding of D-maurotoxin are indistinguishable from those of L-maurotoxin.…”
Section: Discussionmentioning
confidence: 99%